PROTOTIPE SISTEM PENGAMANAN PINTU RUMAH BERBASIS SOLENOID DOOR LOCK, MAGNETIC SENSOR, MIKROKONTROLLER NODEMCU ESP8266 DAN APLIKASI BLYNK - Hanggara, Indira Prabawati; Rakhmadi, Frida Agung (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2020)
This research is motivated by the many cases of theft of assets that occur. Property theft cases continue to occur even though the authorities have been to anticipate criminal acts of theft through existing laws and regulations. Therefore an alternative security system is needed that can reduce cases of theft of property. This research is one of the alternatives for anticipating theft cases. The purpose of this research is making and test a prototype of home door security system based on solenoid door lock, magnetic sensor, NodeMCU ESP8266 microcontroller and Blynk applications. Making the system is divided into two, namely making hardware and software. Making hardware system has three stages. The first stages is to make home mokup, the second stage is connect the sensor to the components use and the last stage is pair the system that has been created into the home mokup. Making software system has two stages. The first stages is make widget in Blynk application and the second stages is make sketch program use Arduino Software. System testing has two variations for finding the percentage of success a system. The two variations are keystrokes test and breaking door test. The result is prototype of home door security system based solenoid door lock, magnetic sensor, NodeMCU ESP8266 microcontroller and the Blynk application have been built and tested for success. The results of testing the success of the door security system obtained a success percentage of 100% for door 1, 2 and 3.